2018
DOI: 10.1002/pbc.27543
|View full text |Cite
|
Sign up to set email alerts
|

Survival and characteristics of pediatric salivary gland cancer: A systematic review and meta‐analysis

Abstract: A systematic search of PubMed, EMBASE, and the Cochrane Library for studies from 2000 to 2017 including children aged 0‐19 with salivary gland cancer was performed. In 19 studies, 749 children (median age of 14.2 years, female to male ratio of 1.4:1) were included; 72% had parotid tumors and 95% underwent surgery, of whom 65% had surgery alone and 24% with adjuvant radiotherapy. Low‐grade and stage mucoepidermoid carcinoma were the most frequent cancer. The 5‐year overall‐ and disease‐free survival was 94% and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 37 publications
(261 reference statements)
1
24
0
Order By: Relevance
“…13 Two SEER database studies (Surveillance, Epidemiology, and End Results) and a meta-analysis summarized the clinical characteristics of pediatric patients with salivary gland carcinomas, emphasizing that a large proportion were low-grade tumors; however, the authors did not compare the patients by risk group, and variables such as T stage and margin status were not uniformly reported. 1,14,15…”
Section: Discussionmentioning
confidence: 99%
“…13 Two SEER database studies (Surveillance, Epidemiology, and End Results) and a meta-analysis summarized the clinical characteristics of pediatric patients with salivary gland carcinomas, emphasizing that a large proportion were low-grade tumors; however, the authors did not compare the patients by risk group, and variables such as T stage and margin status were not uniformly reported. 1,14,15…”
Section: Discussionmentioning
confidence: 99%
“…Complete surgery is the mainstay of treatment, regardless of the tumor type and location 2,21,30,33,35,36,67–69 (Level III; Grade A), and represents a major prognostic factor 9,70–74 . Excision biopsy or tumor enucleation should be avoided due to the risk of tumor seeding (Level III; Grade E).…”
Section: Treatment Recommendationsmentioning
confidence: 99%
“…Major nerve involvement was an independent prognostic factor for poor PFS and DMFS, while a time from surgery to RT >30 days resulted in worse PFS and DMFS. A previous study showed clear tendencies for worsening effects of poor differentiation in SCC and high grade in MEC (14). Other research has shown that high-grade tumor histology is a highly significant predictor of shorter survival in SGC, irrespective of histological subtype (15).…”
Section: Discussionmentioning
confidence: 89%